2018
DOI: 10.1093/nc/niy009
|View full text |Cite
|
Sign up to set email alerts
|

Can hypnosis displace the threshold for visual consciousness?

Abstract: To test the specific effects of hypnosis on the attentional components of visual awareness, we developed a posthypnotic suggestion for peripheral visual inattention inspired on the “tunnel vision” symptom of the Balint Syndrome. We constructed a dual-target visibility and discrimination paradigm, in which single-digit numerical targets were placed both on the hypnotically affected peripheral space and on the remaining undisturbed central area. Results were 3-fold: (i) when compared to participants of Low hypno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Previous studies on the influence of hypnotic suggestions on a visual oddball paradigm have shown that a suggested visual blockade can decrease performance, as well as decrease strength of the correlated P3b signal 21 , a signal associated with frontal-parietal memory load 22 , but found no significant changes in earlier components. Another study, implementing a “tunnel vision” suggestion found that highly suggestible participants reported lower visibility of stimuli, but no change in task performance, indicating that the suggestion’s influence was limited to attendance 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the influence of hypnotic suggestions on a visual oddball paradigm have shown that a suggested visual blockade can decrease performance, as well as decrease strength of the correlated P3b signal 21 , a signal associated with frontal-parietal memory load 22 , but found no significant changes in earlier components. Another study, implementing a “tunnel vision” suggestion found that highly suggestible participants reported lower visibility of stimuli, but no change in task performance, indicating that the suggestion’s influence was limited to attendance 23 .…”
Section: Introductionmentioning
confidence: 99%